Effectiveness of Group Tutoring Service Using Self Management Techiques to Improve High School Students’ Discipline - Okta, Oktatul; S, Neviyarni; Aprinaldi, Eki (Journal of Educational, Health and Community Psychology, 2024)
Discipline is important point for success as a student. However, there are still students who have low discipline, as was found at SMA Negeri 1 Tapaktuan, there were students who often came to school late, wore clothes that did’t comply with the regulations, chatted with friends when the teacher explained, slept when the teacher explained, and scribbled on school facilities. This research aims to analyze the differences in the level of discipline of experimental group students after being given group guidance services using self-management techniques with the control group who were given group guidance services usually provided by teachers at school. The method used is a quantitative approach with a quasi experimental design model non equivalent control group design. The Sample of 16 students was taken using a total sampling technique with low discipline criteria. The instrument uses a Likert Scale model student discipline questionnaire. The research results showed that there was an increase in student discipline after following group guidance using self-management techniques. This means that group guidance services with self-management techniques are effective in improving student discipline. Guidance and guidance teachers at schools can use this service as a way to overcome low student discipline.